2006
DOI: 10.1103/physrevb.73.045420
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium molecular vibrons: An approach based on the nonequilibrium Green function technique and the self-consistent Born approximation

Abstract: We consider the nonequilibrium quantum vibrations of a molecule clamped between two macroscopic leads in a current-carrying state at finite voltages. Our approach is based on the nonequilibrium Green function technique and the self-consistent Born approximation. Kinetic equations for the average populations of electrons and vibrons are formulated in the weak electron-vibron coupling case and self-consistent solutions are obtained. The effects of vibron emission and vibronic instability are demonstrated using f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 29 publications
(21 reference statements)
0
87
0
Order By: Relevance
“…The results obtained for the vibrational excitation show that, except for regions with resonant absorption, the largest current-induced vibrational excitation is obtained for the system with the weakest vibronic coupling. This counterintuitive behavior has been analyzed before for the case of a single electronic state [21,22]. In particular, it has been shown that the vibrational excitation diverges in the limit λ→0 if no other vibrational relaxation processes are active.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The results obtained for the vibrational excitation show that, except for regions with resonant absorption, the largest current-induced vibrational excitation is obtained for the system with the weakest vibronic coupling. This counterintuitive behavior has been analyzed before for the case of a single electronic state [21,22]. In particular, it has been shown that the vibrational excitation diverges in the limit λ→0 if no other vibrational relaxation processes are active.…”
mentioning
confidence: 86%
“…1 (b)). For molecular junctions that are dominated by transport through a single electronic state, these basic processes and the resulting conductance properties have been studied in detail employing a variety of theoretical methods including master equations, scattering theory, nonequilibrium Green's function approaches and path integral methods [7,16,17,18,19,20,21,22,23].…”
mentioning
confidence: 99%
“…Only recently, the nonequilibrium Green's function method 9,10,11,12 , which has been widely used to study the electronic transport, has been applied to study the quantum phononic transport 13,14,15,16,17 . As far as we know, the study of the coupled electronic and phononic transport in nanostructures is rare 18,19,20,21 . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 19, the authors considered the nonequilibrium phonons in molecular transport junctions. Galperin and co-authors analyzed the heat generation and conduction in molecular systems 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1990s inelastic electron tunneling spectroscopy ͑IETS͒ on single molecules was successfully demonstrated using a scanning tunneling microscope ͑STM͒. 13 Later, in the quantum dot regime, measurements on a single C 60 transistor showed features indicating a strong coupling between center-of-mass motion of the molecule and single-electron hopping.…”
mentioning
confidence: 99%